Case Report: A Case of Pediatric Catatonia: Role of the Lorazepam Challenge Test - Ridgeway, Laura; Okoye, Albert; McClelland, Ian; Dhossche, Dirk; Kutay, Deniz; Loureiro, Mario (Frontiers in Psychiatry, 2021)
A case of a 12-year-old boy who developed catatonia is presented. He had no previous psychiatric history but has a family history of affective disorder. An extensive medical workup was negative. Despite a negative lorazepam challenge test, lorazepam was titrated up to 24 mg/day, with resolution of most catatonic symptoms. The case highlights an important point in the management of catatonia that may be a source of confusion, i.e., a positive lorazepam challenge test corroborates the diagnosis of catatonia; however, a negative lorazepam challenge test does not negate the diagnosis of catatonia, and subsequent focused benzodiazepine treatment may still be effective.